2021
DOI: 10.1021/acs.jctc.0c01174
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Analogs to Cholesterol Affect Dimerization of Proteorhodopsin and Modulates Preferred Dimer Interface

Abstract: Hopanoids, the bacterial analogues of sterols, are ubiquitous in bacteria and play a significant role in organismal survival under stressful environments. Unlike sterols, hopanoids have a high degree of variation in the size and chemical nature of the substituent attached to the ring moiety, leading to different effects on the structure and dynamics of biological membranes. While it is understood that hopanoids can indirectly tune membrane physical properties, little is known on the role that hopanoids may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…Poger and Mark and Melo et al investigated the partitioning of HOP in POPC membranes, and found that HOP located in the midplane of the phospholipid bilayer even at proportions as low as 9%. This preferential location was also observed in POPE bilayers …”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Poger and Mark and Melo et al investigated the partitioning of HOP in POPC membranes, and found that HOP located in the midplane of the phospholipid bilayer even at proportions as low as 9%. This preferential location was also observed in POPE bilayers …”
Section: Introductionsupporting
confidence: 73%
“…The previous results indicate that HOP segregated from POPC even at proportions as low as 1%, forming three-dimensional aggregates and inducing less stiff and more expanded films. Bilayers provide a different environment than monolayers, and HOP could accumulate between POPC hemilayers as predicted by simulated experiments. To test this, we prepared giant unilamellar vesicles (GUVs) composed of POPC and 20% HOP, as well as pure POPC, POPC and CHO, or POPC and DP for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PyLipID was also used to identify cholesterol binding sites using a community analysis approach to group residues which simultaneously interact with a bound cholesterol over the course of the trajectories. This method is described in detail elsewhere 53,54 and has been applied to a number of recent examples to characterise lipid binding sites and kinetics [55][56][57] . Since the residue composition of Sites A and B varied slightly with the % cholesterol present in the bilayer, we selected six residues from each site, contacts to which were maintained across all cholesterol concentrations and used these six residues in our subsequent analysis (Supplementary Fig.…”
Section: Binding Site Identificationmentioning
confidence: 99%
“…Microbial rhodopsins typically associate as oligomers in vivo , which is also the case with heliorhodopsins that are known to form dimers ( 5 , 22 ). Indeed, it has been demonstrated that lipid composition of the membrane can directly affect proteorhodopsin dimerization ( 23 ). The presence of MORN-repeats in HeRs exclusively within extreme haloalkaliphilic bacteria (class Dethiobacteria ) may be accounted for via their potential role in stabilizing HeR dimers in conditions of increased membrane fluidity (see Fig.…”
Section: Resultsmentioning
confidence: 99%